Drinking Water Source Protection in the Tampa Bay Region: A Guide for Homeowners - Amy L. Shober (EDIS)
SL-280, a 3-page illustrated fact sheet by Amy L. Shober, familiarizes homeowners in the Tampa Bay region with the local sources of drinking water, potential pollution sources, and actions that can protect the quality of the local drinking water supply. Includes references. Published by the UF Department of Soil and Water Science, February 2009. Revised June 2009.